Japan: World-Class Universities for Social Innovation - Yonezawa, Akiyoshi (International Higher Education, 2018)
A new world-class university policy called the Designated National University scheme was introduced in Japan in 2017. Six national universities are now given a distinguished legal status, differentiating them from all other national universities, and are expected to be competitive with leading universities worldwide. However, the government expects the selected universities to be capable of generating their own income. In light of the uncertainty surrounding the highly complex mechanism linking knowledge activities at universities and industrial commercialization, this appears to be a risk-taking policy.